Epithelial-specific Toll-like Receptor (TLR)5 Activation Mediates Barrier Dysfunction in Experimental Ileitis. Issue 3 (31st January 2017) - Lopetuso, Loris R.; Jia, Ruo; Wang, Xiao-Ming; Jia, Li-Guo; Petito, Valentina; Goodman, Wendy A.; Meddings, Jon B.; Cominelli, Fabio; Reuter, Brian K.; Pizarro, Theresa T.
Abstract : Background: A large body of evidence supports a central role of TLR5 and its natural ligand, flagellin, in Crohn's disease (CD), with the precise mechanism(s) still unresolved. Methods: We investigated the role of flagellin/TLR5 in SAMP1/YitFc (SAMP) mice, a spontaneous model of Crohn's disease-like ileitis. Results: Ileal Tlr5 and serum antiflagellin IgG antibodies were increased in SAMP before the onset of inflammation and during established disease; these trends were abrogated in the absence of colonizing commensal bacteria. Irradiated SAMP receiving either wild-type (AKR) or SAMP bone marrow (BM) developed severe ileitis and displayed increased ileal Tlr5 compared with AKR recipients of either SAMP or AKR bone marrow, neither of which conferred ileitis, suggesting that elevated TLR5 in native SAMP is derived primarily from a nonhematopoietic (e.g., epithelial) source. Indeed, ileal epithelial TLR5 in preinflamed SAMP was increased compared with age-matched AKR and germ-free SAMP. TLR5-specific ex vivo activation of SAMP ileal tissues decreased epithelial barrier resistance, indicative of increased permeability, and was accompanied by altered expression of the tight junction proteins, claudin-3, occludin, and zonula occludens-1. Conclusions: Our results provide evidence that aberrant, elevated TLR5 expression is present in the ileal epithelium of SAMP mice, is augmented in the presence of the gut microbiome, and that TLR5 activation in response to bacterial flagellin results in a deficiency to maintain appropriate epithelial barrier integrity. Together, these findings represent a potential mechanistic pathway leading to the exacerbation and perpetuation of chronic gut inflammation in experimental ileitis and possibly, in patients with Crohn's disease.